The Future of Nursing Care with Artificial Intelligence: Balancing Pros and Cons - Hayder, Israa M.; Younis, Hussain A.; Younis, Hameed Abdulkareem (Journal of Information Systems Research and Practice, 2025)
The integration of artificial intelligence (AI) technologies, such as ChatGPT, into nursing practice, has introduced novel opportunities and challenges. This abstract explores the multifaceted impact of ChatGPT on nursing care, highlighting its potential benefits and pitfalls. ChatGPT serves as a comprehensive knowledge resource, offering nurses instant access to medical information and fostering continuous learning. Additionally, it facilitates educational innovation by providing interactive learning experiences and hands-on training opportunities. This study employed a comprehensive literature review approach to explore the impact of ChatGPT on nursing care. Relevant articles were identified through searches of electronic databases, including PubMed, CINAHL, and Google Scholar, using keywords such as "ChatGPT," "artificial intelligence," "nursing care," and "healthcare." Studies published in peer-reviewed journals between 2010 and 2023 were included in the analysis. The literature review revealed a growing body of evidence on the utilization of ChatGPT in nursing care, highlighting its potential to enhance communication, decision support, and administrative efficiency. Several studies reported positive outcomes associated with ChatGPT adoption, including improved patient satisfaction, increased access to clinical information, and reduced workload for nursing staff. The findings of this study highlight the complex interplay between the promise and pitfalls of ChatGPT integration in nursing care. While AI technologies offer exciting opportunities to augment healthcare delivery, they also present inherent risks that must be addressed proactively. Nurses play a crucial role in navigating the impact of ChatGPT on patient care, advocating for ethical AI use, and preserving the human-centric nature of nursing practice.